Deposition mechanism of polydisperse xanthan gum-stabilized graphene oxide/nano-iron composites in saturated porous medium. (10th November 2020) - Ren, Liming; Chi, Zifang; Dong, Jun; Zhao, Yongsheng; Zhang, Chunpeng
Abstract: Engineered materials (EMs) have shown promise for remediation of groundwater contaminants and the potential application relies on the delivery of aqueous solutions of EMs to a targeted subsurface location or region. Thus, the ability to accurately predict nanoparticle transport and retention in saturated porous media is one of the most technical challenges faced by the design and assessment of potential field-scale environmental applications. Here, a prior prediction model was presented by coupling the effect of Derjaguin–Landau–Verwey–Overbeek (DLVO) interaction, Brownian diffusion, hydrodynamics and interception. Characteristics used in the model were medium size, porosity, injection velocity, size distribution of particles, attachment efficiency, single-collector contact efficiency. The direct comparison of parameterized prior model predictions to experimental measurements was proposed to thoroughly understand deposition mechanism of polydisperse xanthan gum-stabilized graphene oxide/nano-iron composites (XG-nZVI/rGO). The model predicted deposition rate coefficient quantitatively very close to measured rates. When the particle diameter ( d p ) of XG-nZVI/rGO excessed 1.2080 μm, it was retained in the porous medium by interception; When d p < 0.1737 μm, XG-nZVI/rGO would deposite in the porous medium if the kinetic energy ( E k ) it possessed is less than the depth of the secondary energy minimum; When 0.1737 μm < d p < 1.2080 μm, deposition occurred where adhesive torques ( T A ) was in excess of hydrodynamic drag torgues ( T H ) particles subject to. Further, deposition rate was positive correlated with injection concentrations among the range of 0.34–1.70 g/L. Besides, low deposition rates were observed with injection velocities around 0.69 cm/min. Graphical abstract: Image 1 Highlights: Deposition mechanism of polydisperse XG-nZVI/rGO was clarified. Heterogeneity was the key factor determining deposition mechanism of particle. Interception was used to simply quantify straining. A priori model was proposed to correctly predict deposition of XG-nZVI/rGO.